FRI0212 The relationship between brain white matter changes and fatigue in granulomatosis with polyangiitis (GPA; wegener's). (23rd January 2014) - Basu, N.; Jones, G.; Luqmani, R.; Murray, A.; Reid, D.; Macfarlane, G.; Waiter, G.
Abstract : Background: Brain white matter (WM), and more specifically neuronal connectivity is thought to perform a crucial role in the central processing of fatigue. In diseases of the WM, such as multiple sclerosis, fatigue is a common disabling complication. Similarly, fatigue is a principal complaint amongst patients with Granulomatosis with Polyangiitis (GPA), an auto-immune disease which may involve multiple organs including the brain. Although severe brain manifestations resulting from macroscopic damage are uncommon, the possibility of microscopic involvement as an explanation for the high levels of reported fatigue has not previously been investigated. Magnetic resonance (MR) diffusion tensor imaging (DTI) provides a microscopic assessment of potential brain damage measuring the structural integrity of WM by tracking the rate and direction of water molecule diffusion. Data from DTI is presented as fractional anisotropy (FA) values, where reduced FA reflects impaired structural integrity, as is observed in the context of damage, and raised FA reflects increased structural complexity, as is reported in functional disorders such as fibromyalgia where the changes are thought to reflect WM plasticity in response to sustained activation. Objectives: Using both standard and DTI MR techniques, we aimed to test the hypothesis that WM damage was associated with fatigue in patients with GPA. Methods: GPA patients were recruited based on fatigue status; those reporting problems with fatigue for >3 months and scoring >3 on the Chalder Fatigue Scale (CFS) were defined as cases, those without fatigue (<3 on the CFS) were defined as controls. Controls were matched to cases according to age and sex. All subjects were clinically characterised and only those in clinical remission (Birmingham Vasculitis Activity Score=0 for >3months) underwent MR scanning. Standard T1, T2 and FLAIR images were acquired and reported by a radiologist blinded to fatigue status. Specifically, Scheltens' white matter hyperintensity scores (SWMHS) were recorded, a quantitative measure of macroscopic white matter damage. DTI analysis was performed using track based spatial statistics and corrected for multiple comparisons. Mann-Whitney tests were employed to compare the baseline clinical characteristics of cases and controls; differences with a p value of <0.05 were considered significant. Results: Cases (n=14) and controls (n=14) were not significantly different in terms of reported WM hyperintensities (mean SWMHS 5.8±4.5 and 4.9±4.0 respectively). Compared to controls, there were no regions of WM where cases recorded reduced FA. However, cases did record significantly greater FA in the region of the fornix and cingulum fibre tracts. The groups were clinically similar with no significant group differences in relation to vasculitis damage index, disease duration, haemoglobin, creatinine or CRP. Conclusions: We have found no evidence to suggest that either macroscopic or microscopic WM damage is associated with fatigue in patients with GPA. Rather, we identified areas of increased structural complexity which are likely to result from sustained activation secondary to chronic fatigue exposure rather than a direct pathological consequence of the underlying disease. Disclosure of Interest: None Declared